Chemical Constituents and Biological Activities of Garcinia Cuneifolia, Mesua Beccariana and Mesua Ferrea - Mong, Xiao Hui (2005)
Investigations on the stem bark of Garcinia cuneifolia, Mesua beccariana and Mesua ferrea (Guttiferae) have resulted in the isolation of eight compounds. The structures of these compounds were elucidated by using spectroscopic techniques such as nuclear magnetic resonance (NMR), mass spectroscopy (MS), infra red (IR), ultraviolet (UV) and also by comparison with previous reports.